Understanding the Perspective of the Mining-Affected Community on Illegal Gold Mining (PETI) in Gogorea Village, Waeapo District, Buru Regency - Wali, Wulan Sari; Pinoa, Wiclif Sephnath; Riry, Johan (Jurnal Pendidikan Geografi Unpatti, 2024)
This research aims to understand the perspectives of mining communities on illegal gold mining (PETI). They conducted their study in Gogorea Village, Waeapo District, and Buru Regency, using a qualitative method with theoretical foundations to grasp community perspectives. Sampling was done through simple random sampling involving 12 respondents: Village Heads, five local miners, and six non-local miners. Data were collected through observation, interviews, and documentation, then analyzed descriptively using the Likert scale. The results reveal the unique characteristics of PETI in Gogorea Village, where miners use simple and traditional tools, often collaborate, and employ traditional gold refining methods. Although PETI provides income, its severe environmental impacts, including waste, soil, forest, and air pollution, are evident. Ecological protection is necessary for sustainability and community welfare. It is recommended to enforce strict regulations and increase monitoring of PETI activities to mitigate environmental damage. Additionally, providing sustainable economic alternatives for communities is crucial to reducing dependence on illegal mining.